Regulatory pathways linking progenitor patterning, cell fates and neurogenesis in the ventral neural tube - Briscoe, James (The Royal Society, 2007)
The assembly of neural circuits in the vertebrate central nervous system depends on the organized generation of specific neuronal subtypes. Studies over recent years have begun to reveal the principles and elucidate some of the detailed mechanisms that underlie these processes. In general, exposure to different types and concentrations of signals directs neural progenitor populations to generate specific subtypes of neurons. These signals function by regulating the expression of intrinsic determinants, notably transcription factors, which specify the fate of cells as they differentiate into neurons. In this review, we illustrate these concepts by focusing on the generation of neurons in ventral regions of the spinal cord, where detailed knowledge of the mechanisms that regulate cell identity has provided insight into the development of a number of neuronal subtypes, including motor neurons. A greater knowledge of the molecular control of neural development is likely to have practical benefits in understanding the causes and consequences of neurological diseases. Moreover, recent studies have demonstrated how an understanding of normal neural development can be applied to direct differentiation of stem cells in vitro to specific neuronal subtypes. This type of rational manipulation of stem cells may represent the first step in the development of treatments based on therapeutic replacement of diseased or damaged nervous tissue.